AlxGa1−xN/GaN/AlN heterostructures grown on Si(1 1 1) substrates by MBE for MSM UV photodetector applications. (June 2015) - Yusoff, M.Z. Mohd; Hassan, Z.; Hassan, H. Abu; Abdullah, M.J.; Rusop, M.; Pakhuruddin, M.Z.
Abstract: Al x Ga1− x N/GaN/AlN heterostructures on silicon (Si) substrate was developed by nitrogen plasma-assisted molecular beam epitaxy (MBE) and their properties were investigated by scanning electron microscopy (SEM), electron dispersive X-ray (EDX), atomic force microscopy (AFM), high resolution X-ray diffraction (XRD), Raman spectroscopy and Hall effect measurements. High purity gallium (7N) and aluminum (6N5) were used in the Knudsen cells. High purity nitrogen with 7N purity was supplied to radio frequency (RF) source to generate reactive nitrogen species. The nitrogen pressure and a discharge power were kept at 1.5×10 −5  Torr and 300 W, respectively. From SEM measurements, the surface morphology of samples presented 2- and 3-dimensional growth modes. The EDX measurements showed that there were no foreign elements in the grown samples. The HR-XRD measurement has confirmed that the Al x Ga1− x N/GaN/AlN heterostructures samples were epitaxially grown on Si substrate. All the dominant E 2 phonon modes were found in Raman spectra results. Lastly, Al x Ga1− x N/GaN/AlN heterostructures based metal–semiconductor–metal (MSM) UV photodetectors were fabricated and the electrical characteristics of the devices were investigated by using current–voltage ( I–V ) and photo-conductivity measurements. The devices presented good I–V and photoconductivity characteristics.